Pengembangan Alat Bantu Arbor untuk Pembuatan Roda Gigi pada Mesin Frais Vertikal - Widodo, Widodo; Hakim, Rahman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The machining process is included in the classification of metal cutting processes, which are used to change the shape of metal or non-metallic product by cutting, peeling or separating. One of the machines used in this cutting process is a vertical type milling machine. This machine functions to make a product, one of which was a gear. The supporting equipment needed to make this gear was a vertical arbor tool. The material used in the manufacture of this product was a cast carbon steel type using the design method for manufacturing and assembly (DFMA), which began by examining and identifying needs, conceptualizing and designing products and making these products tailored to the dimensional specifications of standard and common cutter modules in the market.Â The results of the manufacture of this tool were directly tested for the manufacture of gears of various sizes and produced products whose deviations were within the tolerance of the measuring instrument, namely in the range 0 to 2%. In addition, the von Mises stress simulation at an engine speed of 150 Rpm, 450 Rpm and 750 Rpm and the resulting maximum stress was still below the yield limit, so it was safe to use.